Exploring the predictors of academic performance: the role of personality, rational beliefs, and self-efficacy - Coşa, Lucica Emilia; Cernat, Vasile (Frontiers in Psychology, 2025)
IntroductionThis study examines the predictive roles of personality traits, rational/irrational beliefs, and self-efficacy in academic performance, while also investigating how these factors interact with gender, residence, and school type.MethodsData were collected from 453 students at George Emil Palade University of Medicine, Pharmacy, Science, and Technology in Târgu Mureş using the Zuckerman-Kuhlman Personality Questionnaire (ZKPQ), the General Self-Efficacy Scale (SES), and the short-form Attitudes and Beliefs Scale (ABSs).ResultsResults revealed that institutional factors, particularly high school type, emerged as the strongest predictors of academic performance. Among the psychological traits, aggressiveness/hostility, impulsive sensation seeking, and rationality significantly predicted academic performance. Notably, impulsive sensation seeking was positively linked to higher performance in female but not male students, while aggressiveness/hostility predicted better performance only among students with high self-efficacy.DiscussionThese findings highlight the potential for tailored intervention programs that take into account gender and personality differences to improve academic outcomes.